2013
DOI: 10.1371/journal.pone.0077481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Screening System for Obesogenic Compounds: Screening of Endocrine Disrupting Compounds and Evaluation of the PPAR Dependency of the Effect

Abstract: Recently the environmental obesogen hypothesis has been formulated, proposing a role for endocrine disrupting compounds (EDCs) in the development of obesity. To evaluate this hypothesis, a screening system for obesogenic compounds is urgently needed. In this study, we suggest a standardised protocol for obesogen screening based on the 3T3-L1 cell line, a well-characterised adipogenesis model, and direct fluorescent measurement using Nile red lipid staining technique. In a first phase, we characterised the assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 52 publications
6
112
1
2
Order By: Relevance
“…PC -Phosphatidylcholines, TAG -triacylglycerols. accumulation assay and was a weak activator of PPAR␥ receptor (Pereira-Fernandes et al, 2013). However, in-vivo studies have shown an accumulation of liver triglycerides and cholesteryl esters with changes in hepatic FA composition in adult mice exposed to low BPA doses; an activation of lipogenesis and cholesterol biosynthesis were pointed out as the major mechanisms involved (Marmugi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC -Phosphatidylcholines, TAG -triacylglycerols. accumulation assay and was a weak activator of PPAR␥ receptor (Pereira-Fernandes et al, 2013). However, in-vivo studies have shown an accumulation of liver triglycerides and cholesteryl esters with changes in hepatic FA composition in adult mice exposed to low BPA doses; an activation of lipogenesis and cholesterol biosynthesis were pointed out as the major mechanisms involved (Marmugi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, Marmugi et al (2012) reported the accumulation of triglycerides and cholesteryl esters in the liver of mice exposed to 50 and 500 g BPA/kg/day. Interestingly, micromolar concentrations of BPA and 4-nonylphenol (4-NP) triggered the differentiation of 3T3-L1 cells in adipocytes (Masuno et al, 2002(Masuno et al, , 2003, and BPA induced the expression of adypocite-specific genes (such are FAS and leptin) (Phrakonkham et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenic potency increased with the linear length of the alkyl chain [29] and was associated with PPARγ activation [30]. It seems increasingly likely that any ligand for PPARγ will be able to influence adipogenesis and obesity [30]. This poses the question as to whether mixtures of such ligands may also be able to stimulate adipogenesis at lower concentrations than each alone, as already has been shown for the estrogenic effects of EDCs on breast cancer cell growth (see Chapter 10).…”
Section: Edcs and Obesitymentioning
confidence: 95%
“…More recently, the alkyl esters of p-hydroxybenzoic acid (parabens) have also been shown to promote adipocyte differentiation in 3T3-L1 cells [29]. Adipogenic potency increased with the linear length of the alkyl chain [29] and was associated with PPARγ activation [30]. It seems increasingly likely that any ligand for PPARγ will be able to influence adipogenesis and obesity [30].…”
Section: Edcs and Obesitymentioning
confidence: 99%
“…high priority: 2,6-di-tertbutylbenzoquinone). Furthermore, receptor gene assays were applied to determine the estrogen (ER), androgen (AR), progesterone (PR), glucocorticoid (GR), thyroid beta (TRβ), peroxisome proliferator gamma (PPARγ) and aryl hydrocarbon receptor (AhR) mediated transactivational activity, since these nuclear receptors are involved in several regulating processes in the human body (Zoeller et al 2012;Pereira-Fernandes et al 2013). Based on this series of bioassays, an overall cumulative toxicity scoring was assigned to each identified compound.…”
Section: Introductionmentioning
confidence: 99%